2014
DOI: 10.1002/2013jd021190
|View full text |Cite
|
Sign up to set email alerts
|

A comprehensive evaluation of precipitation simulations over China based on CMIP5 multimodel ensemble projections

Abstract: Precipitation variability has great economic, social, and environmental impacts across the globe, and in particular in China. This paper evaluates the historical precipitation variability based on 20 general circulation models from the Coupled Model Intercomparison Project Phase 5 (CMIP5) archive over the 20th century relative to two observational data sets and quantifies CMIP5 improvements over CMIP3. Multimodel ensemble means and individual models are assessed. Three future emission scenarios are used (repre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

13
111
1

Year Published

2015
2015
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 188 publications
(131 citation statements)
references
References 97 publications
13
111
1
Order By: Relevance
“…Recently, based on CMIP5 climate models, precipitation was generally projected to increase in China by the end of the 21st century (Wang and Chen, 2014). Moreover, the most significant increases were projected to occur over the Tibetan Plateau and East China in summer, indicating the change in monsoonal circulation in the future (Chen and Frauenfeld, 2014). Precipitation is the main source of increased moisture, and ET o , as a main source of atmospheric water demand, also plays an important role in the hydrologic budget.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Recently, based on CMIP5 climate models, precipitation was generally projected to increase in China by the end of the 21st century (Wang and Chen, 2014). Moreover, the most significant increases were projected to occur over the Tibetan Plateau and East China in summer, indicating the change in monsoonal circulation in the future (Chen and Frauenfeld, 2014). Precipitation is the main source of increased moisture, and ET o , as a main source of atmospheric water demand, also plays an important role in the hydrologic budget.…”
Section: Discussionmentioning
confidence: 99%
“…The AI, as the ratio between ET o and P (Budyko, 1974;Middleton and Thomas, 1992), is a widely used indicator of regional moisture conditions, and high values of the index indicate higher aridity.…”
Section: Meteorological Data and Model Performance Matricmentioning
confidence: 99%
See 2 more Smart Citations
“…This is consistent with Song and Zhou (2014), who examined the simulation of the EASM in CMIP3 and CMIP5 atmosphere-only GCMs and found no evidence for a relationship between model fidelity and resolution (ranging from ∼ 22-500 km). In their analysis of CMIP5 coupled models, Chen and Frauenfeld (2014) also concluded that horizontal resolution did not influence climatological precipitation and IAV over China. On the other hand, Li et al (2015) performed a series of experiments with the Community Atmosphere Model (CAM5) at resolutions of T42 (310 km at the equator), T106 (125 km) and T266 (50 km).…”
mentioning
confidence: 99%